High solid anaerobic co-digestion of household organic waste with cow manure - Khairuddin, Nuruljannah; Abd Manaf, Latifah; Halimoon, Normala; Wan Abdul Karim Ghani, Wan Azlina; Hassan, Mohd Ali (Elsevier, 2015)
Different mixture ratio of household organic waste (HOW) and cow manure (CM) were investigated for biogas production. The objective was to explore possible significant synergistic effect obtained from the combination of these different substrates in Reactor 1 – 4 (R1–4) batch experiment. The highest methane yield, 247 mL/g VS was obtained from R3 and 243 mL/g VS in R4. Co-digestion in R4 increased to 9% for CM and 78% for HOW in methane production. The results clearly demonstrate synergistic effect from nutrient balanced that improves the stability of anaerobic process.